The Effectiveness of ZEP Quiz Game-Based Learning on Descriptive Text Comprehension - Savira Najwa Awwala Arkham; Olyvia Revalita Candraloka (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
EFL reading comprehension of descriptive texts is frequently a considerable issue for secondary students. This study used constructivism to assess the effectiveness of ZEP Quiz, a digital game-based learning platform, in improving descriptive text comprehension. SMAN 1 Mayong used a quantitative method with a quasi-experimental, non-equivalent control group design. The active sample included 67 tenth-grade students, split into two groups: an experimental group (N = 33) that used ZEP Quiz and a control group (N = 34) that received traditional teaching. Data from a validated 22-item reading test were evaluated using the non-parametric Mann-Whitney U test on N-Gain scores. The research found a significant difference in learning improvement (Z = -2.230, p = 0.026 < 0.05). However, unexpected trends showed that the control group achieved a higher progression (Mean Rank = 37.81) than the experimental group (Mean Rank = 27.52). This indicates that ZEP Quiz did not outperform conventional text-based instruction, as gaming mechanics likely imposed an excessive cognitive load that distracted learners from deeper text processing. Therefore, EFL practitioners must carefully balance gamified media with strategic teacher scaffolding to maximize reading outcomes.